THEORETICAL AND EXPERIMENTAL PREREQUISITES FOR DIRECT FORECAST OF HYDROCARBONS BASED ON SEISMIC EXPLORATION DATA (CASE STUDY THE SOUTH CASPIAN AND OTHER BASINS) - FEYZULLAYEV, Akbar; AHMADOV, Tofig; MAMMADOVA, Arzu (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The petrophysical properties of the sedimentary rocks (porosity, permeability, elastic-plastic and acoustic properties, etc.) have been well studied and the results have been sufficiently widely used in the interpretation of geophysical data. Experimental studies completed in recent years as well as intensive technology improvements in data processing and interpretation of seismic data allowed us to explore also the problem of fluid control of petrophysical properties of rocks, which serves as a basis for developing a method of directly forecasting oil and gas accumulations in sedimentary basins. İt is recommended to use a direct seismic method for predicting the productivity of the section in combination with gas-geochemical survey. The aim is to minimize the risk of hydrocarbon exploration in the deepwater part of the South Caspian. Methods. Based on an analysis of worldwide experience and the results of experimental studies in the South Caspian Basin (SCB), the direct seismic methods substantiate the high efficiency of direct forecasting of hydrocarbon accumulations in the sedimentary section. Results. The analysis of direct determination of hydrocarbons using seismic data in other basins, as well as the results of developmental and experimental validation of proposed methodology, allows us to state its sufficient applicability in the geological conditions of SCB. However, considering high economic and technological risks of drilling in the deep part of SCB (development of abnormally high pressures, high cost of exploration wells, which exceeds 100 million), and attempting to minimize them, it would be beneficial to integrate the seismic method with other direct methods, especially with gas-geochemical surveying. Conclusions. The natural exposure of oil and gas on the surface are of great significance to the hydrocarbon exploration since it directly points to the existence of hydrocarbons in sedimentary basins. In the deepwater part of the basin, the presence and nature of oil and gas shows one of the few tools available to assess the prospects of undrilled area. The emergence of new analytical capabilities in recent years allows us to record a very low concentration of migratory gases and increases the efficiency of detection of even low-contrast hydrocarbon anomalies (Elias et al., 2004).